Outdoor thermal comfort within different building blocks - Taleghani, Mohammad; Kleerekoper, Laura; Tenpierik, Martin; van den Dobbelsteen, Andy (A+BE | Architecture and the Built Environment, 2014)
Outdoor thermal comfort in urban spaces is known as an important contributor to pedestrians’ health. The urban microclimate is also important more generally through its influence on urban air quality and the energy use of buildings. These issues are likely to become more acute as increased urbanisation and climate change exacerbate the urban heat island effect. Careful urban planning, however, may be able to provide for cooler urban environments. Different urban forms provide different microclimates with different comfort situations for pedestrians. In this paper, singular East-West and North-South, linear East-West and North-South, and a courtyard form were analysed for the hottest day so far in the temperate climate of the Netherlands (19th June 2000 with the maximum 33°C air temperature). ENVI-met was used for simulating outdoor air temperature, mean radiant temperature, wind speed and relative humidity whereas RayMan was used for converting these data into Physiological Equivalent Temperature (PET). The models with different compactness provided different thermal environments. The results demonstrate that duration of direct sun and mean radiant temperature, which are influenced by urban form, play the most important role in thermal comfort. This paper also shows that the courtyard provides the most comfortable microclimate in the Netherlands in June compared to the other studied urban forms. The results are validated through a field measurement and calibration.